2003
DOI: 10.1055/s-2003-38483
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of P-Glycoprotein-Mediated Multidrug Resistance by Protopanaxatriol Ginsenosides from Korean Red Ginseng

Abstract: The overexpression of P-glycoprotein (Pgp) or the multidrug resistance-associated protein (MRP) confers multidrug resistance (MDR) to cancer cells. MDR cells can be sensitized to anticancer drugs when treated concomitantly with an MDR modulator. In this study, we investigated whether or not ginseng saponins could reverse MDR mediated by Pgp or MRP. The chemosensitization and drug accumulation effects of ginseng saponins such as the total saponin, protopanaxadiol ginsenosides (PDG), protopanaxatriol ginsenoside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 10 publications
3
38
0
Order By: Relevance
“…Glycyrrhizae Radix, at a low concentration of 1 mg/ml, decreased the sensitivity to paclitaxel and Rhodamine123 uptake, presumably by the acceleration of MDR1 function by Glycyrrhizae Radix. 17) The present findings suggest the existence of a modifying action of some herbal extracts on MDR1, and imply the possibility of reversing MDR1-mediated resistance. The detailed investigations using MDR1-overexpressing HeLa cells are ongoing in our laboratory, but the data have not been obtained yet.…”
Section: Discussionsupporting
confidence: 51%
“…Glycyrrhizae Radix, at a low concentration of 1 mg/ml, decreased the sensitivity to paclitaxel and Rhodamine123 uptake, presumably by the acceleration of MDR1 function by Glycyrrhizae Radix. 17) The present findings suggest the existence of a modifying action of some herbal extracts on MDR1, and imply the possibility of reversing MDR1-mediated resistance. The detailed investigations using MDR1-overexpressing HeLa cells are ongoing in our laboratory, but the data have not been obtained yet.…”
Section: Discussionsupporting
confidence: 51%
“…41) The PPT type ginsenosides have been documented to suppress glycoprotein dependent multidrug resistance and increase the sensitivity of cancer cells to anti-cancer drugs. 42) In addition, PPT type ginsenoside metabolites have been shown to increase the effects of anticancer drug by inhibiting breast cancer resistance protein. 43) Fermentation by A. niger and A. oryzae dramatically increased cytotoxicity of KGB on the HT-29 and HepG2 cell lines, which in turn confirmed that ginsenosides in KGB were highly transformed.…”
Section: )mentioning
confidence: 99%
“…For example, ginseng is drug usually used to invigorate vital energy, the main components of it not only affected drug metabolism but inhibited P-gp as well (C.H. Choi et al, 2003;S.W. Kim et al, 2003;S.…”
Section: Meridian Guide Drug and Transportersmentioning
confidence: 99%